2015
DOI: 10.1371/journal.pone.0134795
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Evapotranspiration as a Response to Climate and Vegetation Coverage Changes in Northwest Yunnan, China

Abstract: Climate and human-driven changes play an important role in regional droughts. Northwest Yunnan Province is a key region for biodiversity conservation in China, and it has experienced severe droughts since the beginning of this century; however, the extent of the contributions from climate and human-driven changes remains unclear. We calculated the ecosystem evapotranspiration (ET) and water yield (WY) of northwest Yunnan Province, China from 2001 to 2013 using meteorological and remote sensing observation data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 61 publications
(59 reference statements)
1
23
0
Order By: Relevance
“…Much previous research has demonstrated a positive correlation between temperature and ET in study areas such as the Guanzhong region of Shanxi [51], northeast China [52], and the Songhua River basin [53]. However, the most important factor in the change of ET is precipitation [43] in the Tibetan Plateau and northwest Yunnan [19], which is in agreement with our study both in temporal distribution and in spatial distribution ( Figures 2 and 4(b)). The ET value is highest in the summer, when the precipitation is also largest [54].…”
Section: Dynamics Of Et the Spatial Distribution Of Et Oversupporting
confidence: 91%
See 1 more Smart Citation
“…Much previous research has demonstrated a positive correlation between temperature and ET in study areas such as the Guanzhong region of Shanxi [51], northeast China [52], and the Songhua River basin [53]. However, the most important factor in the change of ET is precipitation [43] in the Tibetan Plateau and northwest Yunnan [19], which is in agreement with our study both in temporal distribution and in spatial distribution ( Figures 2 and 4(b)). The ET value is highest in the summer, when the precipitation is also largest [54].…”
Section: Dynamics Of Et the Spatial Distribution Of Et Oversupporting
confidence: 91%
“…The most common way is to use remote sensing data to calculate the evapotranspiration by employing the surface energy balance with parameters such as meteorological data [18], which has been used in China, including in the northwest of Yunnan province [19]. Long-term estimation methods of evapotranspiration mainly involve water balance [20][21][22], combination, and complementary methods [23,24], and measurement methods mainly involve sap flow, lysimeter, and eddy covariance methods, which underestimate the measurement [25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand accurately the correlation and interaction mechanisms among hydrological variables in the changing environment, and to develop scientific strategies to cope with the changing climate, it is necessary to separate and quantify the contributions of climate change and human activities to hydrological variations (e.g., runoff and drought) [33][34][35] and even ecology elements (e.g., ecosystem evapotranspiration ET, gross primary productivity GPP) [29]. At present, the common models used for evaluating the impacts include Soil Water Assessment Tool (SWAT) model [31], Yellow river water balance model (YRWBM) model [33], Budyko-type equations [34], Penmann-Monteith model [35], and statistical analysis methods [29,36,37] mainly include integration of regression analysis and the double cumulative curve. Recently, statistical analysis methods are paid more attention due to they need less data and parameter calibration compared with hydrological models, and suitable to the data-scare watershed.…”
Section: Discussionmentioning
confidence: 99%
“…Penmann-Monteith model [35], and statistical analysis methods [29,36,37] mainly include integration of regression analysis and the double cumulative curve. Recently, statistical analysis methods are paid more attention due to they need less data and parameter calibration compared with hydrological models, and suitable to the data-scare watershed.…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that afforestation efforts contributed to the vegetation coverage increase in northwestern Yunnan Province. A multivariate linear regression analysis indicated that the factor of vegetation coverage variation explained 14.82% of the ETa variation in this region [20]. …”
Section: Introductionmentioning
confidence: 99%